TESL students’ intention to use AI in academic writing: a research protocol - Ahmad Badri, Ayesha Sofea; Zulkifli, Muhammad Syafiq; Besar Sa’aid, Hafizah (Universiti Teknologi MARA, Kedah, 2025)
In today's educational landscape, academic writing is essential for tertiary students as it reflects their formal ideas, evaluation, and comprehension of their studies. Utilising artificial intelligence (AI) tools is an effective way to enhance academic writing, yet students' intention to adopt AI varies. Recent studies showed that 41% of students do not integrate AI into their education. This variation in AI adoption can be analysed through the Theory of Planned Behaviour (TPB) because it deals with students’ attitude and behaviour towards AI. Currently, there is limited research examining TESL students' intention to use AI in English academic writing through this theoretical lens. Thus, this study investigates the relationship between TPB variables (attitude, subjective norm, and perceived behavioural control) and the intention of TESL students at a semi-private university to use AI in academic writing. The study will employ a quantitative approach, using an anonymous online questionnaire to gather primary data from TESL students. The findings of the study will provide valuable insights into the role of attitudes, social expectations, and students' perceived confidence in using AI tools, which significantly influence their intention to adopt AI for academic writing. The results will contribute to a deeper understanding of factors influencing AI usage in educational settings, offering practical implications for educational policymakers, university administrators, and the field of educational technology. These insights may help shape future initiatives to promote AI adoption in academic writing, addressing existing gaps and supporting students in enhancing their writing practices.